Shape-based image reconstruction using linearized deformations. (1st February 2017) - Öktem, Ozan; Chen, Chong; Onur Domaniç, Nevzat; Ravikumar, Pradeep; Bajaj, Chandrajit
Abstract: We introduce a reconstruction framework that can account for shape related prior information in imaging-related inverse problems. It is a variational scheme that uses a shape functional, whose definition is based on deformable template machinery from computational anatomy. We prove existence and, as a proof of concept, we apply the proposed shape-based reconstruction to 2D tomography with very sparse and/or highly noisy measurements.